2016
DOI: 10.1016/j.healthplace.2016.09.004
|View full text |Cite
|
Sign up to set email alerts
|

Structural inequalities drive late HIV diagnosis: The role of black racial concentration, income inequality, socioeconomic deprivation, and HIV testing

Abstract: In the United States, research is limited on the mechanisms that link socioeconomic and structural factors to HIV diagnosis outcomes. We tested whether neighborhood income inequality, socioeconomic deprivation, and black racial concentration were associated with gender-specific rates of HIV in the advanced stages of AIDS (i.e., late HIV diagnosis). We then examined whether HIV testing prevalence and accessibility mediated any of the associations above. Neighborhoods with highest (relative to lowest) black raci… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

8
57
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
4
2
2

Relationship

1
7

Authors

Journals

citations
Cited by 89 publications
(65 citation statements)
references
References 85 publications
(93 reference statements)
8
57
0
Order By: Relevance
“…Greater health disparities in places with a greater concentration of black Americans is not unique to COVID-19. Similar patterns have been reported for other conditions such as HIV 27 , air pollution 28 , cancer 29 , and low birth weight 30 and may be derived from the fact that in the United States, race often determines place of residence. 31 Ninety-one percent of disproportionately black counties in these analyses are located in the southern United States -a region where most black Americans reside 32 (58%) that also ranks highest in unemployment, uninsurance, and limited health system capacity or investment.…”
Section: Discussionsupporting
confidence: 71%
“…Greater health disparities in places with a greater concentration of black Americans is not unique to COVID-19. Similar patterns have been reported for other conditions such as HIV 27 , air pollution 28 , cancer 29 , and low birth weight 30 and may be derived from the fact that in the United States, race often determines place of residence. 31 Ninety-one percent of disproportionately black counties in these analyses are located in the southern United States -a region where most black Americans reside 32 (58%) that also ranks highest in unemployment, uninsurance, and limited health system capacity or investment.…”
Section: Discussionsupporting
confidence: 71%
“…It may be contrary to expectations that the outbreak rate of a new pathogen, which is able to infect virtually anyone, manifests contextual disparities. But for other conditions, such as HIV and cancer, regional health disparities have been reported before, 32,33 and with the current study we show that contextual factors in the U.S. also create a variation in COVID-19 cases. Our analysis indicates that higher outbreak rates can be found in U.S. states characterized by a higher cultural value of collectivism (coefficient 0.998, confidence interval [0.351; 1.645], p = 0.004).…”
Section: Discussionsupporting
confidence: 79%
“…Alternately, the findings may be due to unobserved confounding or interaction with other sociocontextual factors. For example, a recent study in New York City showed that late HIV diagnosis was high in areas with low black racial concentration and high income inequality and areas with high black racial concentration and low income inequality [81] .…”
Section: Discussionmentioning
confidence: 99%
“…For all models, a-priori we included black racial composition and income inequality given a specific interest based on empirical evidence from prior research [50] . We used multinomial logistic regression and selected the “priority” cluster described above as the reference group.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation